Ser maestra en medio de la guerra: los vínculos y el silencio. El caso de una maestra del departamento de Antioquia, Colombia - Rodríguez Gómez, Hilda Mar (2024)
Colombia is one of the most dangerous countries to be a teacher (GCPEA, 2022). This is due to the large number of attacks on teachers in the country. This violence ends up conditioning the pedagogical subjectivity of teachers. This article intends to explore the configuration of the subjectivity of a teacher in the department of Antioquia, who works in a conflict zone. For this purpose, we divide the text into three moments. In the first, we offer a conceptual overview of pedagogical subjectivity. In the second, we establish a relationship between subjectivity and the silence of this teacher, and we close the text with an analysis of the subjectivity of this teacher and the links with the students and their families.